The Role of Autophagy-related Proteins of Beclin-1/BECN1, LC3II, and p62/SQSTM1 in Melanoma Tumors - Hizomi Arani, Reyhaneh; Mohammadpour, Hadiseh; Moosavi, Mohammad Amin; Muhammadnejad, Ahad; Abdollahi, Alireza; Rahmati, Marveh (Asian Pacific Journal of Cancer Biology, 2022)
Purpose: The prognosis of melanoma depends on early diagnosis and timely treatment. Autophagy plays a dual role in tumor progression. In the early stages, it prevents tumor formation, while in the advanced stages it promotes tumorigenicity. This study aimed at investigating the role of autophagy in different stages of melanoma and evaluating the relationship between autophagy and clinicopathological factors. Methods: ATG5 and BECN1 genes expression in melanoma tumors were evaluated in a retrospective study of 5 years in the cancer institute of Tehran, Iran. The autophagy-related proteins and the correlation with clinicopathological data were also investigated in a tissue microarray series of 52 melanoma tumors following by immunohistochemical staining for the autophagy-associated proteins p62/SQSTM1 (p62), LC3II and Beclin-1/BECN1. The possibility of autophagy biomarkers was also predicted by ROC curve analysis. Results: ATG5 and BECN1 gene expression decreased in melanoma tumors in comparison with tumor margins. However, BECN1 expression at the protein level increased with tumor progression. The expression of LC3II also raised while the p62 level declined as the tumor progressed, suggesting an increased autophagy activity during tumor development. Furthermore, melanoma ulceration was positively correlated with BECN1, LC3II and p62 expression with p<0.05, though the melanoma mitotic rate and thickness did not significantly correlate with autophagy–related proteins expression. Conclusions: Autophagy-related proteins are suggested as potential prognostic factors in melanoma and could be considered as a therapeutic target.